Strategi Penguatan dan Pengembangan Pendidikan Karakter Siswa Sekolah Menengah Atas Negeri 15 Takengon Binaan Negeri Antara - Ramadan Ramadan; Hamdan Hamdan (Medan Resource Center, 2025)
Character education remains a critical challenge in secondary education, particularly in efforts to develop human resources with strong moral integrity and civic responsibility. This study examines strategies for strengthening and developing character education at State Senior High School 15 Takengon under the guidance of Negeri Antara. Employing an applied research orientation, this field-based study adopts a qualitative approach to investigate real conditions and social phenomena related to character education as they naturally occur within the school environment. Data were collected through direct engagement with key educational stakeholders to explore strategic implementation, institutional roles, and practical challenges. The findings indicate that character education is systematically reinforced through the implementation of eighteen core character values embedded in the school’s vision and mission, which guide its educational goals and functions. Responsibility for character development involves collaborative efforts among the principal, vice principals, teachers of Islamic Religious Education and Civic Education, all subject teachers, and the Intra-School Student Organization. The study further reveals that no significant obstacles impede implementation, as existing challenges are constructively addressed through reflective and spiritual practices such as muhasabah and zikir. Overall, the study argues that a collaborative, value-based, and reflective institutional culture constitutes an effective strategy for strengthening character education in secondary education.